Perbedaan Kepadatan Benih dan Nutrisi Organik terhadap Produktivitas Green Fodder Jagung : The Effect of Differences in Seed Density and Organic Nutrients on the Productivity of Maize Green Fodder - Tera Fit Rayani; Annisa Hakim; Yuni Resti; Artiqie Gita Yuardi; Yasinta Septiari; Nur Rachmy Fazryah; Faradisa Syafrin Maulida; Shafa Salsabila (Jurnal Agroekoteknologi dan Agribisnis, 2024)
Hydroponic green fodder is a method for producing forage for livestock in a short time (approximately 7–8 days) without soil. It can be an alternative source of high–quality forage to increase the productivity of ruminant livestock. This research aims to compare differences in seed density and the addition of organic nutrients in the form of shallot skins to the productivity of maize green fodder. Fodder planting is done using a hydroponic system with an automatic watering system. The variables measured were fresh and dry biomass production, conversion of green fodder to seeds, plant height, and nutrient content in corn seeds and green fodder. The experimental design used was a 3 x 2 completely randomized factorial design with treatment factors in the form of seed density (1,25; 1,5; and 1,75 kg/m2) and organic nutrition (soaking with tap water and soaking with shallot skin). The results showed that the production of fresh biomass, dry biomass, and plant height were significantly different (P<0,05) influenced by seed density. Total fresh and dry biomass increased with increasing seed density (P<0,05). Plant height increases as seed density decreases (P<0,05). Soaking seeds using shallot skins did not have a significant effect on the productivity of corn green fodder. A seed density of 1,5 kg/m2 produces the best productivity in green fodder corn